2021
DOI: 10.3390/pr9091598
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Thermal Degradation Behaviors and Kinetic Mechanisms of Typical Hardwood and Softwood in Oxygenous Atmosphere

Abstract: In order to utilize woody biomass effectively for bioenergy and chemical feedstocks, the comparative thermal degradation behaviors and kinetic mechanisms of typical hardwood (beech wood) and softwood (camphorwood) were studied at various heating rates in air. The Kissinger-Akahira-Sunose approach combined with the Coats-Redfern approach was employed to estimate the kinetic triplet. Softwood degradation began and ended at lower temperatures than hardwood. Compared with softwood, the maximal reaction rate of har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…In particular, E is the energy barrier that allows one to define the chemical reaction to be overcome as well as its feasibility. 43,44 It has been shown that the reaction proceeds more efficiently at lower activation energies. Figures 7-9 display the iso-conversion diagrams obtained at different heating rates, from which the instantaneous value of E at different conversion rates can be calculated from the individual slopes according to the linear regression equations.…”
Section: Determination Of Activation Energymentioning
confidence: 99%
“…In particular, E is the energy barrier that allows one to define the chemical reaction to be overcome as well as its feasibility. 43,44 It has been shown that the reaction proceeds more efficiently at lower activation energies. Figures 7-9 display the iso-conversion diagrams obtained at different heating rates, from which the instantaneous value of E at different conversion rates can be calculated from the individual slopes according to the linear regression equations.…”
Section: Determination Of Activation Energymentioning
confidence: 99%
“…The heating rate increases to a higher rate and then gradually decreases to the set heating rate, so an exponential decaying trigonometric function (shown in Equation ( 19)) was used to fit the experimental heating program. First, the actual heating rate curve at 10 K min −1 was fitted using Equation (19). The same fitting exercise was performed for the data obtained at heating rates of 5 K min −1 and 20 K min −1 .…”
Section: Inverse Modeling Of the Dsc Data For The Fr_pu_aerogelmentioning
confidence: 99%
“…The characterization of material flammability frequently relied on a thermogravimetric analysis (TGA) experiment [17][18][19] and these are the most common technique used in such measurements. A milligram-size sample and relatively slow heating rates were adopted in these experiments, and thus the heat and mass transport inside the sample was assumed to be negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Electrocatalytic conversion of G-type and S-type phenolic compounds from different tree species in a heteropolyacid fluidized system 5 [40], camphorwood [41], and Cunninghamia lanceolata [42]. S-type phenolic compounds are originated from hardwood tree species, e.g., poplar [43], beech [44],…”
Section: Introductionmentioning
confidence: 99%